A cognitive task analysis of the teacher skills and knowledge required for differentiated instruction in secondary education - Meutstege, Kyra; Vrielink, Marlijn; van Geel, Marieke; Visscher, Adrie J. (Frontiers in Education, 2023)
Providing differentiated instruction (DI) is a complex teacher task that many secondary school teachers do not master well. In the current study, a cognitive task analysis of this teacher task was conducted by analysing how expert teachers do this and why, resulting in an inventory of the necessary teacher skills and knowledge for providing DI, and a description of the factors that influence the complexity of DI. The results of this analysis show what providing DI in secondary education entails, which is valuable for designing teacher professional development programs for DI at that level.